2021
DOI: 10.1002/jcp.30291
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell‐derived extracellular vesicles conditionally ameliorate bone marrow failure symptoms in an immune‐mediated aplastic anemia mouse model

Abstract: Acquired forms of Aplastic anemia (AA) are characterized by T cell‐mediated immune disease resulting in bone marrow (BM) failure and marrow hypoplasia. In these cases, it is a major challenge to modulate autoreactive T cell activity and thereby decrease the pro‐inflammatory cytokine storm. Emerging evidence indicates that extracellular vesicles derived from mesenchymal stem cells (MSC‐EVs) control and modulate immunity. The therapeutic potential of MSC‐EVs has not been investigated in acquired AA. Hence, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The MSC‐derived extracellular vesicles were then isolated and purified according to an established protocol. [ 24 ] Transmission electron microscopy (TEM) imaging showed spherical morphology of MSC‐sEVs (Figure 2D) with an average diameter around 100 nm (Figure 2E), which had no significant difference compared to MSC‐sEVs‐PD‐L1. They contained extracellular vesicles‐associated proteins, e.g., CD63, CD9, and MSCs specific marker CD73 (Figure 2F).…”
Section: Resultsmentioning
confidence: 99%
“…The MSC‐derived extracellular vesicles were then isolated and purified according to an established protocol. [ 24 ] Transmission electron microscopy (TEM) imaging showed spherical morphology of MSC‐sEVs (Figure 2D) with an average diameter around 100 nm (Figure 2E), which had no significant difference compared to MSC‐sEVs‐PD‐L1. They contained extracellular vesicles‐associated proteins, e.g., CD63, CD9, and MSCs specific marker CD73 (Figure 2F).…”
Section: Resultsmentioning
confidence: 99%
“…As far as the mechanisms, MSC-EV immunomodulation is governed by proteins, including growth factors, interleukins, and also miRNAs, such as miR-21-5p, miR-223, miR-146a and miR-199a, whose expression is increased [45,49,50]. In a mouse model, treatment with MSC-EVs ameliorated significantly the immune destructions and confirmed the importance of the non-coding miRNAs also in the clinical developments [50]. Other treatments exacerbate various aspects of neuropathology.…”
Section: Immunitymentioning
confidence: 99%
“…The use of MSC-EVs for therapy of diseases has become relevant in many cases including encephalomyelitis and multiple sclerosis of the brain. The same vesicles also provide more potent therapeutic strategies for other immune-related disorders [50,52,53].…”
Section: Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Gholampour et.al report manifested that MSC‐EVs improve BM deficiency and attenuate AA development by modifying immune responses in a mouse model of AA. They revealed that miR‐126a, miR‐146a, miR199a, and miR‐223 in MSC‐EVs have an inhibitory activity on the proliferation of T cells, as well as the IFN‐γ and TNF‐α cytokine expressions [ 90 ].…”
Section: Introductionmentioning
confidence: 99%